2021
DOI: 10.3390/brainsci11121612
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Sex Hormones and Circulating Growth Differentiation Factor-15 in Male Patients with Major Depressive Disorder

Abstract: The interaction between the endocrine system and inflammation is crucial pathogenesis of depression. Our study aimed at exploring the possible relationship between sex hormones and growth differentiation factor-15 (GDF-15), a common indicator of inflammation in male patients with major depressive disorder (MDD). Methods: GDF-15 levels of 121 male MDD patients were compared with 105 healthy subjects with the help of a Cobas 8000 automatic chemiluminescence immunoanalyzer. Results: (1) MDD patients showed higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(47 reference statements)
1
3
0
Order By: Relevance
“…This is in accordance with the previous finding that older male patients had higher GDF15 levels than female patients [35]. Although underlying mechanisms are not clear so far, this might be explained by sex hormone effects on GDF15 [36].…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with the previous finding that older male patients had higher GDF15 levels than female patients [35]. Although underlying mechanisms are not clear so far, this might be explained by sex hormone effects on GDF15 [36].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, Schwarz et al 53 identified a subgroup of schizophrenia patients with hormonal abnormalities, including increased testosterone. It has been hypothesized that testosterone might be protective because of its anti-inflammatory properties, 54 aligning with the growing recognition of inflammation in mental illness. 55 Our MVMR analysis confirmed the anti-inflammatory effect of testosterone, as CRP's effect decreased.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that androgen may be associated with GDF‐15 expression 20–22 . In addition, studies have linked the increased expression of GDF‐15 with testosterone deficiency in men with coronary artery disease, and shown a correlation between high GDF‐15 levels and low testosterone in other diseases such as depression 23,24 . However, there are currently no reports on the relationship between GDF‐15 and testosterone deficiency in men with T2DM.…”
Section: Introductionmentioning
confidence: 97%
“…[20][21][22] In addition, studies have linked the increased expression of GDF-15 with testosterone deficiency in men with coronary artery disease, and shown a correlation between high GDF-15 levels and low testosterone in other diseases such as depression. 23,24 However, there are currently no reports on the relationship between GDF-15 and testosterone deficiency in men with T2DM. This study therefore investigated male patients with T2DM to examine the relationship between high levels of GDF-15 and testosterone deficiency.…”
Section: Introductionmentioning
confidence: 99%